El naufragio de la cazatorpedera Rosales (1892) : juicio al comandante Leopoldo Funes - Oyarzábal, Guillermo Andrés (2008)
Fil: Oyarzábal, Guillermo Andrés. Pontificia Universidad Católica Argentina; Argentina